AUTOIMMUNE POLYGLANDULAR SYNDROME PREVALENCE IN TOLUCA, MEXICO - CONCEPCIÓN CARRILLO LE; RODRÍGUEZ PIÑA MD; PINEDA GONZÁLEZ MG; GARCÍA OCAMPO F; MENDIETA ZERÓN H (Avicenna Tajik State Medical University, 2022)
Objective: Autoimmune polyglandular syndromes (APS) are endocrinopathies whose main characteristic is the loss of immune tolerance. The objective of this work was to report the APS prevalence in an Internal Medicine Service from Toluca, Mexico. Methods: This was a descriptive and retrospective study. Medical files from the service of Internal Medicine at Ciprés Grupo Médico CGM SC (CGM), Toluca, Mexico, in a period of 11 years were analyzed. The prevalence of APS was obtained taking into account all the patients seen in the mentioned period and in particular considering only the following diseases: diabetes mellitus, thyroiditis and Addison's disease. Results: From 2000 clinical files, five cases (0.25%) are presented according to the criteria and clinical manifestations. APS detection among patients who were treated for endocrine pathology (diabetes mellitus = 807, thyroiditis = 473, and hypocortisolism = 5) were 5 in 1285 (0.38%). Conclusion: APS-2 is the most common type of APS in a common Internal Medicine service in Toluca, Mexico.